"Romancing" the Popular Politics: A Religious Aspect of Popular Politics in Tanauan City, Batangas, the Philippines - Soon, Chuan Yean (2009)

(untitled)
In 2004 during my initial research period in Manila as well as in Tanauan City, Batangas Province, many friends advised me to be wary because Tanauan is widely known as a "drug haven" and a city notorious for its violent environment, especially because of its local politics.